How to Disappear : A Memoir for Misfits - Fallowell, Duncan (Book collections on Project MUSE., 2013)
The author sets out to odd corners of the world in pursuit of some extraordinary and improbable characters who were momentarily famous - or infamous - and then simply disappeared. The first to disappear is the author himself - to a ghostly hotel on a Mediterranean island. His subjects, though unmet or hardly met, live for the reader with remarkable vividness, such as the German artist who bought a large island in the Hebrides and vanished immediately afterward, to the astonishment of its inhabitants. The author tracks down the recluse who inspired Evelyn Waugh's creation Sebastian Flyte, the legendary love object of Waugh's novel Brideshead Revisited, who wants both to forget the past and to cling to it. He even pursues the ultimate disappearance - the death of Princess Diana - and the miasma of shock, wonder, and grief that followed, writing, "Mystification is absolutely essential to our feeling of being alive."